2012
DOI: 10.1586/era.12.16
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Met pathway in lung cancer

Abstract: Dysregulation of Met signaling has been implicated in the initiation, progression and metastasis of human cancers, and therefore represents an attractive target for anticancer drug development. Met is overexpressed in non-small-cell lung cancer and its lack of staining in normal lung tissue makes it an attractive target. To date, erlotinib and gefitinib have established themselves as first-line therapy for non-small-cell lung cancer patients whose tumors harbor an EGF receptor gene mutation, and hence, it is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…Soon afterwards, more researchers reported that Met amplification and its phosphorylation are associated with both primary and acquired resistance to EGFR TKI therapies in NSCLC patients (Guo et al, 2008;Suda et al, 2010;Belalcazar et al, 2012). Together, these reports implicate Met as a potentially effective therapeutic target to reverse resistance to this important class of drugs in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Soon afterwards, more researchers reported that Met amplification and its phosphorylation are associated with both primary and acquired resistance to EGFR TKI therapies in NSCLC patients (Guo et al, 2008;Suda et al, 2010;Belalcazar et al, 2012). Together, these reports implicate Met as a potentially effective therapeutic target to reverse resistance to this important class of drugs in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Binding of HGF to MET triggers receptor dimerization and transphosphorylation, which lead to conformational changes of the receptor with subsequent activation of the tyrosine kinase (TK). Activation of the TK domain in turn mediates downstream signaling via the PI3K/AKT, RAS-RAC/RHO, MAPK, and phospholipase C pathways (8,9). During embryogenesis, MET receptors are expressed on epithelial cells as well as on muscle precursor cells to mediate epithelial-to-mesenchymal transition which is essential for limb bud development (10).…”
Section: Introductionmentioning
confidence: 99%
“…In preclinical models, lung cancer cell lines with MET amplification were shown to be dependent on MET signaling for growth and survival (25). As a result, many new MET inhibition compounds (including antibody inhibition, small-molecule inhibitors, and others) have entered clinical trials (9). However, to date the frequency of MET amplification in NSCLC remains controversial and it ranges from 3% to 10%, depending on the detection technique, cutoff criteria, and selection of samples (15)(16)(17)(18)26).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical benefit was demonstrated in NSCLC patients with tumors expressing elevated levels of Met protein (≥ 50% tumor cells having 2-3+ IHC staining) who were treated with onartuzumab and erlotinib, and a durable complete response was observed in a metastatic gastric cancer patient with high MET polysomy and Met protein expression detected by immunohistochemistry who was treated with onartuzumab. [52][53][54][55] CE-355621 appears to exhibit superior binding and neutralizing activity for its target in biochemical assays compared with onartuzumab. The affinity of bivalent CE-355621 for native c-Met is ~56 pM and for recombinant c-Met ECD is ~200 pM; whereas, the affinity of monovalent 5D5 (onartuzumab) for c-Met is ~4 nM.…”
Section: Discussionmentioning
confidence: 99%